The Influence of Deferred Taxes and Tax to Book Ratio on Company Financial Performance - Kadek Wulandari Laksmi P; IGN Oka Ariwangsa; Komang WIdhya Sedana Putra P (UPI YPTK Journal of Business and Economics, 2024)
The reason for conducting this research is to understand the relationship of deferred tax variables and tax to book ratio influence a company's financial performance. The independent variables in the research conducted this time are deferred tax and tax to book ratio, then the fixed variable in the current research is financial performance. This research applies a quantitative approach, multiple linear regression is used as a statistical test, and to analyze the data the classical assumption test is used. By using manufacturing companies operating in the food and beverage sector that have been listed on the Indonesia Stock Exchange during 2020–2022 as the research population and sample. A total of 17 companies were used as purposive samples, which means the number of samples used was 51 observation data because. This research was conducted using the SPSS Version 25 program. The final results obtained imply that deferred tax has a positive effect with a coefficient value of 54.652 and a significant value of 0.014 < 0.05 and the tax to book ratio has a coefficient value of 3.866, and a significant value of 0.000 < 0.05, it can be concluded that the tax to book ratio variable also has a significant positive effect on financial performance.